NATURAL LANGUAGE VS. CONTROLLED VOCABULARY / LANGAGE NATUREL VS. VOCABULAIRE CONTROLE - Svenonius, Elaine (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see pdf